Pain and possibilities of physiotherapy for impingement syndrome in the shoulder joint (Perioperaciina Medicina, 2024)
Introduction: Shoulder problems are the second most common disease of the musculoskeletal system.Background: The most common cause of these problems is impingement syndrome. The aim of our work was to point out the possibilities of conservative treatment for impingement syndrome. In this work, we tried to draw attention to the deterioration in the quality of life caused by shoulder problems and we wanted to improve the range of motion in the shoulder to flexion, abduction, and reduce pain due to the chosen physiotherapy procedures. Our work has a theoretical part, in which we approach the impingement syndrome, its examination and treatment.Material and methods: In the practical part, we used a clinical study with a questionnaire method to achieve the goal of our work. Th e group consisted of 20 patients with impingement syndrome, in whom we used manual therapy, kinesiotherapy, electrotherapy, and Kinesio taping. Using a questionnaire, we were able to assess how much impingement affects the quality of life.Results: Due to the methods we chose, we managed to improve the range of motion of the arm, where the average value at the initial measurement was 119.25° to flexion and 113° to abduction. In the output measurement, the average value up to flexion was 163.25° and up to abduction 165.75°.Conclusion: We also reduced the overall pain, which averaged 6.90 at baseline and 2.90 at the end. Based on our results we recommend a combination of methods to be used in impingement
Keywords: pain; impingement syndrome; shoulder plait; rotator cuff; physiotherapy